La elaboración de proyectos curriculares de centro en el marco de un currículo de ciencias abierto - Carmen, Luís M. del (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The new curricular proposeds put foreword by the Ministry of Education are characterized, among other things, by being based on a flexible, open design, whose development requires active participation of the teaching teams in each school. The characteristics of this model are analysed as well as the necessary conditions for its viability with special reference to science teaching. The problem of organization and grading educational contents are emphesized.